Beyond the GUI in agriculture : a bibliographic review, challenges and opportunities - Rodríguez, Andrés; Fernández, Alejandro; Hernández Hormazábal, Jorge (2018)
Different reasons have lead to an increased interest in ICTs applications to the agriculture, like precision farming or agricultural robotics. However the GUI remains the most common interface today, a host of other interfaces are becoming increasingly prevalent, such as speech based, gestural, haptics, multimodal, etc. This work presents a bibliographic review about the inclusion of nontraditional interactions (named beyond the GUI interfaces after Kortum ) for different operations in the agricultural fields, a qualitative analysis and some challenges and opportunities found
Formato de archivo PDF. -- Este documento es producción intelectual de la Facultad de Informática - UNLP (Colección BIPA/Biblioteca)
International Conference on Human Computer Interaction (19na : 2018 : Palma de Mallorca, España)
Keywords: AGROINFORMÁTICA; DISEÑO CENTRADO EN EL USUARIO